1998
DOI: 10.4269/ajtmh.1998.58.625
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo reversal of chloroquine resistance in Plasmodium falciparum with promethazine.

Abstract: The effect of combining promethazine with chloroquine was examined against Plasmodium falciparum in vitro in the Aotus-P. falciparum model and in bioassays from volunteers given promethazine. The combination of chloroquine plus promethazine (1 ϫ 10 Ϫ6 M) reversed chloroquine resistance in standard P. falciparum clones and patient parasite isolates from Nigeria. The combination reduced the 50% inhibitory concentrations (IC 50 s) for chloroquine against resistant parasites by 32-92%. Coadministration of prometha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 25 publications
1
61
0
Order By: Relevance
“…[7][8][9][10][11] A small number of heterologous challenges have been performed in the past using P. falciparum strains in Aotus monkeys. These studies, performed in other species of Aotus, also showed that previous infection provided protection from subsequent challenge with the same strain.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] A small number of heterologous challenges have been performed in the past using P. falciparum strains in Aotus monkeys. These studies, performed in other species of Aotus, also showed that previous infection provided protection from subsequent challenge with the same strain.…”
Section: Discussionmentioning
confidence: 99%
“…6 For more than 40 years, the Panamanian Aotus ( Aotus lemurinus. lemurinus ) has been used to adapt new strains of malaria [7][8][9] study its biology, [10][11][12] pathogenesis of its infection, [13][14][15] and to test the efficacy and pharmacokinetics of antimalarial compounds [16][17][18][19][20][21][22][23][24][25][26][27] against these new strains. More recently, this model has also been used to test the efficacy and immunogenicity of antimalarial vaccines through the use of repeated challenge, 28 plasmid DNA vaccines, [29][30][31][32] temperature-sensitive mutants, 33 synthetic peptides, 34 recombinant proteins, [35][36][37] and even to test the immunogenicity of hepatitis B DNA vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of chloroquine resistance is calculated as the IC 50 observed in the presence of various concentrations of NP30 divided by the control (no NPE added) chloroquine IC 50 (274 Ϯ 56 nM). Values greater than 1 indicate that the particular NPE rendered the P. falciparum parasites less sensitive to chloroquine, while values less than 1 indicate that the particular NPE sensitized P. falciparum to chloroquine (17). Nonlinear analysis of the chloroquine IC 50 at known NP30 concentrations indicated that a concentration of approximately 1 M (0.0002% on a weight/volume basis) resulted in a 50% decrease in the degree of chloroquine resistance of the parasites.…”
Section: Resultsmentioning
confidence: 99%
“…The initial observation that drug resistance in P. falciparum could be modulated by verapamil (16) has led to reports that antipsychotics (e.g., chlorpromazine [1]), histamine (H-1) receptor antagonists (e.g., promethazine [17] and chlorpheniramine [2]), and other agents can reverse chloroquine resistance in vitro and in animal models (3). While these observations suggest that chloroquine combined with a second agent can be used to treat malaria, these agents have the disadvantage of being pharmacologically active compounds with multisystemic effects that may result in a variety of side effects.…”
mentioning
confidence: 99%